Pandangan Syekh Abdul Qadir Jailani Terkait Kepemimpin Sufistik - Risna Fauziah; Devi Nurlaili (Prodi Tasawuf dan Psikoterapi Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2021)
Sufism as a science of Islamic teachings provides guidelines to direct humans to a path that is able to bring a servant closer to his Creator. Some of the teachings of Sufism are applied in aspects of human life, one of which is in the aspect of leadership. Although sometimes the leadership aspect does not state the characteristics of a leader taken from the value of Sufism. This article discusses the values of Sufism according to the teachings of Sheikh Abdul Qadir Jailani in becoming a leader. To become a Sufism-based leader one must be able to apply the values of Sufism. The teachings of Sufism used in this article are the teachings of the famous Sufi figure Sheikh Abdul Qadir Jilani. The teachings of Sufism contain several behaviors, namely asceticism, patience, pleasure, gratitude, and qona’ah. From some of these behaviors contain different meanings at the same time in their application. These values will later lead and direct a leader to become a leader who upholds noble character and becomes closer to God. This article aims to add insight and knowledge to the author and those who read it.